Depression and clinical progression in spinocerebellar ataxias. (January 2016) - Lo, Raymond Y.; Figueroa, Karla P.; Pulst, Stefan M.; Perlman, Susan; Wilmot, George; Gomez, Christopher; Schmahmann, Jeremy; Paulson, Henry; Shakkottai, Vikram G.; Ying, Sarah; Zesiewicz, Theresa; Bushara, Khalaf; et al.
Abstract: Background: Depression is a common comorbidity in spinocerebellar ataxias (SCAs) but its association with ataxia progression is not well understood. Objectives: To study the prevalence and influence of depressive symptoms in SCAs. Methods: We studied 300 participants with SCA 1, 2, 3 and 6 from the Clinical Research Consortium for Spinocerebellar Ataxias (CRC-SCA) and repeatedly measured depressive symptoms by the 9-item Patient Health Questionnaire (PHQ-9) along with other clinical features including ataxia, functional status, and quality of life every 6 months for 2 years. We employed regression models to study the effects of depressive symptoms on clinical progression indexed by Scale for Assessment and Rating of Ataxia (SARA), Unified Huntington's Disease Rating Scale Part IV (UHDRS-IV) and EQ5D after adjusting for age, sex and pathological CAG repeats. Results: Comorbid depression is common in SCAs (26%). Although the baseline prevalence of depression was similar among different SCA types, suicidal ideation was more frequently reported in SCA3 (65%). Depressive symptoms were associated with SARA scores but did not significantly progress over time within 2 years or deteriorate by increased numbers of pathological CAG repeats. The effects of depression on ataxia progression varied across different SCA types. Nevertheless, depression had consistently negative and significant impact on functional status and quality of life in all SCAs, even after accounting for ataxia progression. Conclusions: Depressive symptoms are not simply the consequence of motor disability in SCAs. Comorbid depression per se contributes to different health outcomes and deserves more attention when caring patients with SCAs. Highlights: Depression is common in SCAs and depressive symptoms do not progress over 2 years. Suicidal ideation is more prevalent in SCA3. The effects of depression on ataxia progression vary across different SCA types. Depression has negative impact on functional status and quality of life in all SCAs, after accounting for ataxia progression.